PENGARUH BIAYA PRODUKSI DAN BIAYA PEMASARAN TERHADAP LABA PERUSAHAAN PADA PT PP LONDON SUMATERA INDONESIA,TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Irpan Januarsah; Jubi Jubi; Ady Inrawan; Debi Eka Putri (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The purpose of this research is to know the description of production costs, marketing costs and profit of the company as well as the influence of the image of the production costs, marketing costs against earnings the company PT PP London Sumatra Indonesia Tbk, which is listed on the stock The Effect Of Indonesia. The research was conducted using a descriptive analysis of the qualitative and Quantitative Descriptive Analysis. This research was conducted based on secondary data from the consolidated statements of comprehensive income statement PT PP London Sumatra Indonesia Tbk obtained from Indonesia stock exchange.Research results can be concluded that, the image production costs and marketing costs tend to rise while the company's earnings are likely to decline. Linear regression results the production costs and marketing costs are insignificant negative effect against the profits of the company at PT PP London Sumatra Indonesia Tbk. correlation coefficient test results and the determination of the production costs and marketing costs with profit the company has a very strong relationship and production costs and marketing costs affect the profit of 67.1% the rest is explained by other factors not included in the regression model. Test results showed that the hypothesis H0 is accepted which means production costs and marketing costs take effect is not significantly to profit either simultaneously or partial.Advice that can be given is the company should use the full costing method to determine the value of the production cost, charge transport and rent to the buyer to lower marketing costs and profit responsibility for controlling production costs and marketing costs. Keyword: Production Costs, Marketing Costs and Profits of the Company